Activated adaptive immune system in dissected bicuspid aortic valve aortas: trigger for dissection?. (25th November 2020) - Staal, A.H.J; Cortenbach, K.R.G; Gorris, M.A.J; Geuzebroek, G.S.C; Wisse, L.J; Textor, J; Srinivas, M; Morshuis, W.J; De Vries, I.J.M; De Ruiter, M.C; Van Kimmenade, R.R.J
Abstract: Background/Introduction: Bicuspid aortic valve (BAV) is associated with ascending aorta aneurysms and dissections. Presently, genetic factors and pathological flow patterns are considered responsible for aneurysm formation in BAV. Despite, indication for preventive surgery is presently only defined by vessel diameter which is poor marker for dissection, as it does not take other processes responsible for the vulnerability of the aorta into account. Purpose: Inflammation is not considered a player in BAV aortopathy. We introduce a quantitative immunohistochemistry (IHC) approach to sensitively look at the potential role of both the innate and adaptive immune system in BAV aortopathy. Methods: Dilated (n=8), non-dilated (n=14) and dissected (n=4) BAV ascending aortas were collected during surgery or from post-mortem donors. Median time from symptoms to surgery for dissections was just over 4 hours. Tissue was stained with a novel 8-colour IHC technique allowing for simultaneous visualization of 6 markers per slide, completed with DAPI nuclear counter-stain and elastin fiber autofluorescence. One panel focused on the adaptive immune system (identifying B cells and classic dendritic cells type 2 (cDC2s) and phenotyping T cells), and the other on the innate immune system (assessing macrophage polarization and neutrophil extravasation). All cells were identified and comprehensively phenotyped using automated quantitative analysis. Results: Aneurysm formation was associated with an organized and consistent increase of lymphocytes in the adventitia. B cell follicles and helper T cell expansion were identified, suggestive of a targeted adaptive immune response (Fig. 1a). Only dissected aortas showed a statistically significant increase of helper T (p=0.3) and cDC2s (p=0.3) in the media, when compared to non-dilated and dilated samples (Fig. 1b). The short time between dissection symptoms and surgery suggests these cells were present before the dissection occurred. Furthermore, aneurysms and dissections are associated with a shift in macrophage phenotype to the more aggressive M1-like subset. In summary, we found that a progression of aggressive immune cells in the adventitia and media was correlated to a progression in disease state; from normal to dilated to dissected. Conclusions: Aorta dilatation in patients with BAV is associated with an expansion of B and helper T cells in the adventitial compartment without changes in the media. This result might indicate an antigen-driven adaptive immune response. Only dissections show an increase in helper T cells and cDC2s in the media, together with polarization of macrophages to a more M1-like phenotype. We hypothesize that antigen-specific helper T cells expand in the adventitia, migrate to the media, and then potentiate macrophages which can eventually lead to tissue degeneration. These associations could shine light on the final step in the deterioration of the aorta towards a dissection. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): TTW-NWO open technology grant (STW-14716), ERC-2014-StG-336454-CoNQUeST